ANALISIS POTENSI PENGEMBANGAN LAJUR SEPEDA TERINTEGRASI BRT DI DAERAH PERBUKITAN GUNUNGPATI KOTA SEMARANG - Suseno, Dhony Priyo; Kurniawan, Achmad; Utomo, Danang Setyo (Politeknik Negeri Semarang, 2023)
The bike lane in Semarang city has the potential to be developed even though the topography is contoured by hills that divide the city into lower Semarang and upper Semarang. This study aims to determine the potential location of the bike lane development so that the bike mode in lower Semarang can be integrated with the Trans Semarang BRT to upper Semarang, or vice versa, especially to the Semarang State University (UNNES) campus area in Gunungpati district. The BRT integrated bike mode is expected to be able to make the city of Semarang a